JANG OETAMA: HADJI OMAR SAID TJOKROAMINOTO DALAM PERSPEKTIF POLITIK ISLAM: Perspektif Politik Islam - Iwan Prasetiyo (LP3M Sekolah Tinggi Agama Islam Ma'arif Magetan, 2020)
H.O.S Tjokroaminoto is often known as a national teacher among the nation's founders (Founding Father), born on August 16, 1882 to be precise in Bakur village, Sawahan, Madiun. Tjokro is a very egalitarian figure to his fellow man. He was one of the many Muslim leaders of his era who participated in fighting for the interests of the Muslims, who at that time were shackled by the existence of freedom by Dutch colonialism. So repressive that it covers all aspects of the life of the indigenous people. He is the leader of SI (Sarekat Islam). Sarekat Islam is a mass organization that was born in the early twentieth century. The birth of SI also could not be separated from the interference of K.H Samanhoedi. At first this organization was called SDI (Sarekat Dagang Islam) which was only oriented towards trade competition.